Physical activity and quality of life in women with breast cancer – a cross-sectional study Atividade física e qualidade de vida em mulheres com câncer de mama – um estudo transversal Actividad física y calidad de vida en mujeres con cáncer de mama-un estudio transversal - Boing L.* (2018)
© 2018, Redprint Editora Ltda. All rights reserved.Introduction: Breast cancer treatment can cause different side effects on the quality of life of women. Physical activity, in turn, can reduce these side effects. Objective: To investigate the physical activity and quality of life of women during and after breast cancer treatment. Methods: Sample of 174 women (57.0±9.5 years) during or after clinical treatment for breast cancer. Interview questionnaire composed of general information, physical activity (IPAQ short version) and quality of life (EORTC QLQ-C30 and BR23). For statistical analysis chi-squared test or Fisher’s exact test, student’s t-test for independent samples, Mann-Whitney U test and multiple logistic regression analyses (p <0.05). Results: Most women did not achieve the physical activity guidelines, particularly those undergoing clinical treatment. Results showed longer walking time, moderate physical activity, vigorous physical activity, moderate + vigorous physical activity, and total physical activity among the women following completion of treatment. The quality of life scores were also higher among women after clinical treatment. Logistic regression indicated that every 10-minute increment to walking time results in a 19% decrease in the probability of worse functional capacity and a 26% decrease in the probability of worse symptoms associated with treatment side effects. Conclusion: During treatment, women with breast cancer undertake less physical activity and have worse quality of life. Walking appears to be an effective type of physical activity for these women, improving quality of life during and after breast cancer treatment. Level of evidence II; Prognostic studies-Investigation of the effect of patient characteristics on the disease outcome.